Comparison of physical activity levels and musculoskeletal disorders among academicians with different chronotypes - Demir, Oguzhan Bahadir; Taskin Yilmaz, Feride (Health Promotion & Physical Activity, 2025)
Chronotype is one of the factors affecting individuals’ health behaviors. This descriptive and comparative study aimed to identify the chronotype of academicians and determine their physical activity levels and musculoskeletal disorders according to chronotype. Of the academicians, 23.9% (n = 47) were morning type, 58.4% (n = 115) were intermediate type, and 17.7% (n = 35) were evening type. Academicians with morning chronotype were more likely to have a moderate physical activity level (p < 0.05). Academicians frequently experience pain, aches and discomfort in the upper back, neck and lower back areas. However, there was no statistically significant difference between musculoskeletal disorders of academicians in terms of chronotype (p > 0.05). It is recommended that physical activity be increased in academics with evening chronotype, precautions be taken for common musculoskeletal disorders, and the effects of chronotype on the musculoskeletal system be examined in a larger sample group.